HUBUNGAN TINGKAT PENGETAHUAN KADER TENTANG PENGUKURAN ANTROPOMETRI DENGAN KETRAMPILAN DALAM MELAKUKAN PENGUKURAN PERTUMBUHAN BALITA DI POSYANDU KELURAHAN SONOREJO KECAMATAN SUKOHARJO - SUSAN ERAWATI (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2024)
Integrated healthcare center is a form of health effort community resources which is managed and organized from, by, for and with the community in implementing health development. Cadres' knowledge of anthropometry is very important because it will have an impact on cadres' skills in measuring the growth of toddlers. From the results of preliminary survey observations at 4 integrated healthcare center who had anthropometric measurements, 36 children (28%) had measurement errors. This study aims to determine the relationship between the level of cadres' knowledge about anthropometric measurements and their skills in measuring the growth of toddlers at integrated healthcare center, Sonorejo Village, Sukoharjo District, Sukoharjo regency